Colwellia psychrerythraea Strains from Distant Deep Sea Basins Show Adaptation to Local Conditions - Techtmann, Stephen M.; Fitzgerald, Kathleen S.; Stelling, Savannah C.; Joyner, Dominique C.; Uttukar, Sagar M.; Harris, Austin P.; Alshibli, Noor K.; Brown, Steven D.; Hazen, Terry C. (Frontiers in Environmental Science, 2016)
Many studies have shown that microbes, which share nearly identical 16S rRNA genes, can have highly divergent genomes. Microbes from distinct parts of the ocean also exhibit biogeographic patterning. Here we seek to better understand how certain microbes from the same species have adapted for growth under local conditions. The phenotypic and genomic heterogeneity of three strains of Colwellia psychrerythraea was investigated in order to understand adaptions to local environments. Colwellia are psychrophilic heterotrophic marine bacteria ubiquitous in cold marine ecosystems. We have recently isolated two Colwellia strains: ND2E from the Eastern Mediterranean and GAB14E from the Great Australian Bight. The 16S rRNA sequence of these two strains were greater than 98.2% identical to the well-characterized C. psychrerythraea 34H, which was isolated from arctic sediments. Salt tolerance, and carbon source utilization profiles for these strains were determined using Biolog Phenotype Microarrays’. These strains exhibited distinct salt tolerance, which was not associated with the salinity of sites of isolation. The carbon source utilization profiles were distinct with less than half of the tested carbon sources being metabolized by all three strains. Whole genome sequencing revealed that the genomes of these three strains were quite diverse with some genomes having up to 1600 strain-specific genes. Many genes involved in degrading strain-specific carbon sources were identified. There appears to be a link between carbon source utilization and location of isolation with distinctions observed between the Colwellia isolate recovered from sediment compared to water column isolates.